Urban Expansion and Its Effect on Agricultural Technology Adoption of Smallholder Peri-Urban Farmers in Tigray Region, Ethiopia - Weldearegay, Shishay Kahsay; Tefera, Mesay Mulugeta; Feleke, Solomon Tsehay (Caraka Tani: Journal of Sustainable Agriculture, 2021)
In the rapidly growing world, where farming land is shrinking due to horizontal urban expansion and development-induced projects, agricultural productivity should grow by 70% to meet food needs. Spatial urban expansion in developing countries, not exceptional to Ethiopia, puts immense pressure by taking peri-urban fertile agricultural land for the purpose of development. This paper examines whether urban expansion increases or decreases the agricultural technology adoption capacity of smallholder peri-urban farmers. Households were clustered into displaced and non-displaced, and data were collected from 341 households, 101 of whom were displaced and 240 households were non-displaced. Descriptive statistics and econometric model were employed to explore the role of urban expansion in technology adoption of smallholder peri-urban farmers. The multivariate probit result shows that urban expansion decreases the tendency of displaced smallholder peri-urban farmers to participate in irrigation and adoption of a generator but urban expansion does not increase or decrease displaced households’ tendency to adopt beehive and practice row sawing. Generally, urban expansion decreases the affinity of smallholder peri-urban farmers to adopt agricultural technologies. Therefore, policymakers, particularly the Bureau of Agriculture should intensively work and train displaced smallholder peri-urban farmers on the benefit of agricultural technologies to improve agricultural productivity and use the remaining plot of farmland sustainably. Besides strong monitoring and follow-up are required to avert the negative ramifications of development-induced displacement.